PEMODELAN 3 DIMENSI KAWASAN TAMBANG MENGGUNAKAN TEKNOLOGI TERRESTRIAL LASER SCANNER DAN FOTOGRAMETRI UAV - Hafizh Arrasyad, Abyan
Topographic measurements of mining areas using the Terrestrial Laser Scanner (TLS) tool have several weaknesses, namely, there are safety issues because they have to set up tools directly in the area of observation object and it also takes a long time. With the development of Unmanned Aerial Vehicle (UAV) photogrammetry technology, it is hoped that it will become an alternative to topographic measurements in the mine area, which can cover the weakness of TLS. This final project aims to obtain the results of the accuracy of UAV photogrammetry measurements and evaluate the results of the implementation of topographic measurements of the mining area using the UAV photogrammetry method as a material for making work instructions for measuring the topography of the mine area using UAV photogrammetry. The study was conducted at the PT Berau coal mine lokasi in a disposal area of approximately 30 hectares. Data acquisition begins with the measurement of the Ground Control Point or abbreviated as GCP, followed by the acquisition of UAV and TLS photogrammetric measurements at the same time, the UAV photogrammetric data processing is carried out with various GCP and TLS configuration schemes into a Digital Terrain Model (DTM), then the analysis is carried out, by assuming the TLS DTM as true data. Based on the results of the analysis, the vertical accuracy of UAV photogrammetry with various GCP configurations, including the configuration of 4 GCPs which are only at the boundary of the research area, is still within the tolerance of the 1:1000 scale map, which is below 10 cm. Then for the difference in volume percent formed between DTM from photogrammetry and TLS, which is 0.13%, this is still within the tolerance of American Society for Testing and Materials (ASTM), which is 2%. It is hoped that the resulting work instructions, based on the results of the evaluation of this study, can be applied to topographic measurements of mining areas using UAV photogrammetry.